(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The production of heat and power in many countries in the world is mainly based on the burning of fuels, especially water boilers, and gas-fired boilers. Therefore, practical developments in reusing the flue gas energy of water boilers in district boiler houses have been increasing all around the world. Why? Overall, the temperature of released gases from water boilers to the atmosphere is over the dew point of water in waste gases. And it is obvious that recovery of the thermal energy of flue gases increases the efficiency of boilers and supplies energy-saving. Although examination of energy utilization is the search for the minimum consumption of energy. This paper deals with the potential of recovering waste heat emitted by the hot water boiler in district boiler houses. As water boilers are the major component in these industries, it makes it sensible to evaluate the technical features and measure the energy efficiency of boilers.